2011
DOI: 10.1590/s1678-91992011000300014
|View full text |Cite
|
Sign up to set email alerts
|

Renal and vascular effects of Crotalus durissus cumanensis venom and its crotoxin fraction

Abstract: Abstract:In this study, we evaluated the actions of Crotalus durissus cumanensis venom (CDCmV), and its crotoxin (Crtx) fraction, on renal and vascular functions in Wistar rats. In isolated perfused kidneys, CDCmV (10 µg/mL) significantly increased the perfusion pressure (PP) from 110.7 ± 2.4 to 125.3 ± 2.8 mmHg after 30 minutes. This effect was accompanied by an increased renal vascular resistance (RVR) from 5.4 ± 0.1 to 6.2 ± 0.2 mmHg/mL.g ). Both CDCmV and Crtx reduced the percentage of tubular transport of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Th results of cytotoxic effects showed that the venom was toxic to cells because it significantly reduced viability in concentrations of 50 and 100 mg/mL compared to the control with an IC 50 of 169.5 μg/mL. This value for IC 50 is higher in relation of others species of snakes, such as Bothrops leucurus and Crotalus durissus cumanensis with 1.25 and 5.38 μg/mL, respectively [22] , [23] .…”
Section: Discussionmentioning
confidence: 89%
“…Th results of cytotoxic effects showed that the venom was toxic to cells because it significantly reduced viability in concentrations of 50 and 100 mg/mL compared to the control with an IC 50 of 169.5 μg/mL. This value for IC 50 is higher in relation of others species of snakes, such as Bothrops leucurus and Crotalus durissus cumanensis with 1.25 and 5.38 μg/mL, respectively [22] , [23] .…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand, in a more recent study, no effects were observed 12 h after treating rat hearts with crotoxin [ 30 ]. The data on crotoxin’s vascular effects are also inconsistent; while in one work, it was shown that crotoxin induced contractions in Sprague Dawley rat ARs both with and without an endothelium [ 31 ], no effect of this toxin in AR assays was observed in another study [ 32 ]. To clarify this issue, we decided to study the effects of the heterodimeric PLA 2 HDP-1, which is homologous to crotoxin.…”
Section: Introductionmentioning
confidence: 99%